PEMBINAAN KEJUJURAN SISWA MELALUI PEMBELAJARAN KITAB BAHR AL-ADAB - Sani Insan Muhamadi (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2015)
The purpose of this study is to get the ideas of the values that contained in the kitab Bahr Al-Adab and its learning process. The method used is a descriptive analytic with qualitative approach, while the data collection techniques used in this research is the analysis of the contents of the kitab, observation, interviews and documentary study. The study found that: The Kitab Bahr Al-Adab contains very positive character values. The process of learning is performed by the method of lecture, discussion, sociodramatic and inquiry methods. The outcome of learning is, the students were able to honest inside and outside the school. The factors that support in fostering students’ honesty are the vision, mission andobjectives of schools, exemplary of pesantren’s staff, curriculum structure, the activities carried out in schools, as well as involvement in activities in the community. While the factors that hinder, internal factors such as school rules that are not too strict, and there are still students who have difficulty in understanding mufrodat/vocabulary in the kitab Bahr Al-Adab. External factors such as the influence of social, technological, and moral values that began to fade in the community.